Ocean acidification thresholds for decapods are unresolved - McElhany, Paul; Busch, D. Shallin (Frontiers in Marine Science, 2024)
A published analysis of ocean acidification thresholds for decapod crustaceans highlights data showing the negative effects of low pH on many species. However, the methods used in the paper have substantial flaws that call into question the proposed thresholds. The quantitative metrics calculated for the meta-analysis are uninformative with respect to pH sensitivity, which raises concerns about the validity of the thresholds developed by the expert opinion process. We recommend against using the published thresholds and for a reanalysis of the data to identify new thresholds.